2020
DOI: 10.1111/jonm.13120
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient safety climate by nurses in Slovak Public and private hospitals

Abstract: Brborović, Brumen, & Mustajbegović, 2014). Patient safety is considered an international priority area with a focus on prevention strategies aimed at reducing the risk of adverse events or near misses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Several contextual factors should be taken into account while translating nurses’ ideal roles in PC into clinical practice. Important prerequisites which were also already discussed in the literature were: sufficient education [ 32 , 33 ], knowledge (more pharmacology and pharmacotherapeutics) [ 34 , 35 ], an interprofessional collaborative approach [ 1 , 36 ], confidence in nurses [ 37 , 38 ], an open blame-free culture with clarity of team composition and roles [ 39 , 40 ], equality between professionals [ 41 ], adjusted legislation [ 42 ], readiness of professionals and patients to allow nurses to have responsibilities in PC [ 43 ], and a manageable workload leaving “time to care” [ 44 , 45 ]. Lack of time, shortage of nurses, absent legal frameworks and limited education and knowledge were described as main threats.…”
Section: Discussionmentioning
confidence: 99%
“…Several contextual factors should be taken into account while translating nurses’ ideal roles in PC into clinical practice. Important prerequisites which were also already discussed in the literature were: sufficient education [ 32 , 33 ], knowledge (more pharmacology and pharmacotherapeutics) [ 34 , 35 ], an interprofessional collaborative approach [ 1 , 36 ], confidence in nurses [ 37 , 38 ], an open blame-free culture with clarity of team composition and roles [ 39 , 40 ], equality between professionals [ 41 ], adjusted legislation [ 42 ], readiness of professionals and patients to allow nurses to have responsibilities in PC [ 43 ], and a manageable workload leaving “time to care” [ 44 , 45 ]. Lack of time, shortage of nurses, absent legal frameworks and limited education and knowledge were described as main threats.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies in other Latin American countries (Arrieta et al , 2018) and Europe (Gurková et al , 2020) have found stronger perceptions of patient safety culture perceived in private institutions than in public institutions. This suggests that perceptions of patient safety conditions are not determined solely by a country's cultural or political history or level of economic development.…”
Section: Discussionmentioning
confidence: 80%
“…Regarding the use of these instruments in the Czech Republic and Slovakia, only the HSOPS has been tested on a sample of registered nurses in the Czech and Slovak hospital environment (e.g. [32][33][34][35]. However, HSOPS questionnaire was validated for the conditions of the Czech nursing practice revealing the same factor structure as original version (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, HSOPS questionnaire was validated for the conditions of the Czech nursing practice revealing the same factor structure as original version (32). Recently, the validation study of the HSOPS was also conducted within the Slovak nursing practice; nevertheless indicating the eight factor structure (33). To the authorsḱ nowled ge, other instrument measuring patient safety culture has not been used within these two countries.…”
Section: Discussionmentioning
confidence: 99%